Curcumin Exerts Antinociceptive Effects in Cancer-Induced Bone Pain via an Endogenous Opioid Mechanism - Zhao, Guanghai; Shi, Yongqiang; Gong, Chaoyang; Liu, Taicong; Nan, Wei; Ma, Lin; Wu, Zuolong; Da, Chaoming; Zhou, Kaisheng; Zhang, Haihong (Frontiers in Neuroscience, 2021)
Cancer pain is one of the main complications in advanced cancer patients, and its management is still challenging. Therefore, there is an urgent need to develop novel pharmacotherapy for cancer pain. Several natural products have attracted the interest of researchers. In previous studies, curcumin has proved to exhibit antitumor, antiviral, antioxidant, anti-inflammatory, and analgesic effects. However, the analgesic mechanism of curcumin has not been elucidated. Thus, in this study, we aimed to elucidate the antinociceptive potency and analgesic mechanism of curcumin in cancer-induced bone pain. Our results showed that consecutive curcumin treatment (30, 60, 120 mg/kg, i.p., twice daily for 11 days) produced significant analgesic activity, but had no effect on the progress of the bone cancer pain. Notably, pretreatment with naloxone, a non-selective opioid receptor antagonist, markedly reversed the antinociceptive effect induced by curcumin. Moreover, in primary cultured rat dorsal root ganglion (DRG) neurons, curcumin significantly upregulated the expression of proopiomelanocortin (Pomc) and promoted the release of β-endorphin and enkephalin. Furthermore, pretreatment with the antiserum of β-endorphin or enkephalin markedly attenuated curcumin-induced analgesia in cancer-induced bone pain. Our present study, for the first time, showed that curcumin attenuates cancer-induced bone pain. The results also suggested that stimulation of expression of DRG neurons β-endorphin and enkephalin mediates the antinociceptive effect of curcumin in pain hypersensitivity conditions.